Antena Ring Sirkular dengan Kemampuan Penekanan Higher Order Mode - Rheyuniarto Sahlendar Asthan; Achmad Munir (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
This paper presents the development of a circular ring-shaped antenna with ability to suppress higher order mode. An S-shaped is added into the ring in order to satisfy the goal of the antenna development. The upper and lower edges of the ring are excited differentially using two ports in order to have symmetrical radiation pattern. Each port is directly connected to a 50 Ω SMA connector using microstrip feeding line. The antenna is designed with an FR4 dielectric substrate with the dimension of 85.4 mm × 85.4 mm and intended to work at the center frequency of 0.9 GHz. The proposed antenna is compared with the conventional circular ring-shaped antenna to observe the antenna performances in term of higher order mode suppression. In addition, optimization is carried out by varying physical antenna parameters. The measurement result shows that circular ring-shaped antenna with S-shaped element can suppress the higher order mode frequency of 19.55 dB and work properly at the desired frequency of 0.9 GHz. The measured impedance bandwidth for the reflection coefficient (S11) below −10 dB is 251 MHz with fractional bandwidth (fBW) of 27.89%. The symmetrical radiation pattern in E-plane with maximum power density at the boresight is obtained at the frequency of 0.9 GHz and 1.94 GHz. The measured 3 dB beamwidths of 0.9 GHz and 1.94 GHz in E-plane are 99.4o and 100.5o, respectively.